Thermic implications of topography: suggestion about a thermo-topographic parameter - Gandullo, J. M. (Forest Systems, 1997)
In a previous paper (Gandullo, 1974), a sunshine parameter, evaluating light intensity from hill slope and terrain aspect, was developed. This paper presents a new sunshine parameter development trying to assess sunny and shady aspects from the thermic point of view, considering that the maximum daily temperatures occur between two and three hours in the afternoon